2019
DOI: 10.20547/jfer1904205
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Debt and Economic Growth: Evidence from Pakistan

Abstract: The present study aims to analyse the link between external debt, domestic debt and economic growth for Pakistan. To serve the purpose, the study uses the data for the time period from 1987 to 2018. Various econometric techniques i.e, fully modified ordinary least squares model, dynamic ordinary least squares model have been employed to estimate the proposed model. The empirical findings suggested that there exist a negative relationship between growth and debt whether it is external or domestic. The study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This suggests that external debt service has a detrimental effect on Egypt's resources. Rawat (2019) analysed the link between external debt, domestic debt and economic growth for Pakistan from 1987 to 2018 using fully modified ordinary least squares model. Empirical findings suggested that there exist a negative relationship between economic growth and debt whether it is external or domestic, thereby confirming the debt overhang theory…”
Section: Empirical Review Effect Of External Debt On Economic Growthmentioning
confidence: 99%
“…This suggests that external debt service has a detrimental effect on Egypt's resources. Rawat (2019) analysed the link between external debt, domestic debt and economic growth for Pakistan from 1987 to 2018 using fully modified ordinary least squares model. Empirical findings suggested that there exist a negative relationship between economic growth and debt whether it is external or domestic, thereby confirming the debt overhang theory…”
Section: Empirical Review Effect Of External Debt On Economic Growthmentioning
confidence: 99%